Clinico-epidemiological Profile of Children with Diphtheria in Tertiary Care Hospital of Nepal - Basnet, Srijana; Shrestha, Laxman; Bajracharya, Luna (Journal of Nepal Paediatric Society, 2022)
Introduction: This study was conducted with the aim to describe the clinical presentation of diphtheria in children, relationship between clinical disease and immunization status, complications of the disease and adverse events due to anti diphtheria serum (ADS). Methods: All patients admitted at Tribhuvan University Teaching Hospital, Kathmandu from July 2016 to November 2018 with clinical diagnosis of diphtheria were included in this study. Results: There were total 12 children and age ranged from five to 15 years, out of which seven (58%) were males and five (42%) were females. All of them were immunized except one whose immunization status was unknown. All of them had tonsillopharyngeal diphtheria. Four patients (33%) also had nasal and five (42%) patients had additional laryngotracheal diphtheria. Seven patients had bull neck on presentation. Four patients had airway obstruction due to laryngotracheal diphtheria requiring tracheostomy. Throat swab for Corynebacterium Diphtheria by Albert stain and Gram stain were positive in 10 patients, and in nine, diagnosis was confirmed by culture. Six patients (50%) were given anti diphtheria serum (ADS) out of which four patients (66.66%) developed anaphylaxis. Myocarditis was the commonest complication seen in four patients (25%). All children with myocarditis developed complete heart block (CHB) and none of them survived. Conclusions: Tonsillopharyngeal diphtheria was the most common clinical presentation and myocarditis was highly fatal complication. This study emphasizes on the need for careful surveillance, early laboratory confirmation and careful administration of ADS in patients with clinical diagnosis of diphtheria.